19 The Colonial Records of the State of Georgia 104, 108 (2d ed. 1910) - (:unkn) unknown (My University, 1778)
"every person liable to appear and bear Arms at any Muster, exercise or training hereby appointed , pursuant to the directions of this Act, shall constantly keep and bring with him, to such training , exercising or Muster, one good Gun, Bayonet, hanger , sword or hatchet , a Cartouch Box, twelve Cartridges a powder horn and half pound of Powder , with at least twenty four pounds of Lead, a Worm , pricker and four Flints each,"
Keywords: REQUIRED POSSESSION